Budidaya Lebah Madu Trigona pada KTH “Maju Berkah” Dusun Apit Aiq Batulayar - Lombok Barat - Dewi Rispawati; Mey Susanti AS; Siti Yulianah M. Yusuf; Vidya Yanti Utami; Basuki Srihermanto (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2021)
This Community Service is entitled "Trigona Honey Bee Cultivation at KTH "Maju Berkah" Apit Aiq Batulayar Hamlet - West Lombok". The purpose of this Community Service is so that the managed cultivation business is growing and bringing about a better change impact on improving the welfare of its members and the surrounding community, increasing motivation and cooperation in the context of managing and developing the honey bee business carried out, increasing the income and welfare of group members. and the surrounding community so that they are able to overcome family economic problems, increase members' awareness in dealing with social, economic and environmental problems. The partner in this community activity is the Forest Farmers Group (KTH) “Maju Berkah”. This community activity method is carried out in 3 stages, namely 1. Preparation and Socialization to KTH “Maju Berkah and Local Village Community Members, 2. Implementation of Community Service Activities, 3 Monitoring and Evaluation of Community Service Activities Results. As a result of this community service activity, KTH "Maju Berkah" can understand the development of Trigona honey bee cultivation and how to market Trigona honey bee products and can contribute, skills, knowledge and experience to members of the Forest Farmers group and local community members "Maju Berkah" so that can develop Trigona honey bee cultivation.